Novel Multimodal Management of Post-Partum Synchronous Metastatic Pulmonary EBV-Associated Lymphoepithelioma-Like Carcinoma (LELC)—A Case Report - Montserrat Pazos; Chukwuka Eze; Kathrin Kahnert; Maria Delius; Amanda Tufman; Irene Alba-Alejandre; Marcus Unterrainer; Jens Neumann; Thomas Kirchner; Farkhad Manapov (Diagnostics, 2021)
Primary Epstein-Barr-Virus (EBV)-associated pulmonary lymphoepithelioma-like carcinoma (LELC) is an aggressive rare cancer. Higher incidences have been observed in Asian sub-populations. Multimodal treatment paradigms have emerged as promising novel strategies in the management of advanced NSCLC. In this report, we describe the case of a 34-year-old female patient of Asian origin with a post-partum initial diagnosis of pulmonary LELC. Multimodal treatment with chemoimmunotherapy and hypofractionated irradiation to the primary tumour and main metastatic sites led to a favourable response demonstrating that radiotherapy may potentially augment anti-tumour immunity. To the best of our knowledge, this is the first case report on this novel therapy strategy of multi-site hypofractionated radiotherapy and chemoimmunotherapy for metastatic pulmonary EBV-associated LELC.